2019
DOI: 10.1002/pld3.171
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana gene annotated by the locus tag At3g08860 encodes alanine aminotransferase

Abstract: The aminotransferase gene family in the model plant Arabidopsis thaliana consists of 44 genes, eight of which are suggested to be alanine aminotransferases. One of the putative alanine aminotransferases genes, At3g08860, was attributed the function of alanine:glyoxylate aminotransferase/β‐alanine:pyruvate aminotransferase based on the analysis of gene expression networks and homology to other β‐alanine aminotransferases in plants. It was earlier demonstrated that At3g08860 is specifically upregulated in respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Alanine aminotransferase (AlaAT) is a complex pathway, act as a survival mechanism in Lotus, Prunus, grapevine and Arabidopsis against waterlogging stress (53,69,70,71). In this pathway, previously produced pyruvate from glycolysis reacts with glutamate (Glu) to form 2-oxoglutarate by alanine aminotransferase (AlaAT) (Fig.…”
Section: Alanine Aminotransferase Pathway and Tca Cyclementioning
confidence: 99%
“…Alanine aminotransferase (AlaAT) is a complex pathway, act as a survival mechanism in Lotus, Prunus, grapevine and Arabidopsis against waterlogging stress (53,69,70,71). In this pathway, previously produced pyruvate from glycolysis reacts with glutamate (Glu) to form 2-oxoglutarate by alanine aminotransferase (AlaAT) (Fig.…”
Section: Alanine Aminotransferase Pathway and Tca Cyclementioning
confidence: 99%
“…In addition to alanine, β-alanine, a non-proteinogenic amino acid and precursor of various biochemical molecules, also occurs in plants as a stress-response molecule, for example in heat or hypoxia [ 76 ]. The metabolism of L-alanine and β-alanine are linked because L-alanine can act as an amino donor in the synthesis of β-alanine by the β-alanine/L-alanine aminotransferase.…”
Section: Discussionmentioning
confidence: 99%
“…PYD4 (AT3G08860) belongs to the aminotransferase gene family, and it functions as an alanine:glyoxylate aminotransferase/β-alanine:pyruvate aminotransferase ( Parthasarathy et al , 2019 ). PYD4 is up-regulated in response to osmotic stress and has been shown to be putatively involved in β-alanine metabolism ( Parthasarathy et al , 2019 ). Studies have identified that PYD4 is involved in multiple processes in plants, such as changes in light and carbon availability ( Parthasarathy et al , 2019 ).…”
Section: Additional Genes Potentially Playing a Role In The Oas Responsementioning
confidence: 99%
“…PYD4 is up-regulated in response to osmotic stress and has been shown to be putatively involved in β-alanine metabolism ( Parthasarathy et al , 2019 ). Studies have identified that PYD4 is involved in multiple processes in plants, such as changes in light and carbon availability ( Parthasarathy et al , 2019 ). PYD4 is localized in the mitochondria or the peroxisome ( Niessen et al , 2012 ) and it is down-regulated in the microarray of Hubberten et al (2012b) , where OAS is induced internally; however, in sulfur deficiency microarrays and RNA-seq, PYD4 is co-regulated with the OAS cluster genes ( Fig.…”
Section: Additional Genes Potentially Playing a Role In The Oas Responsementioning
confidence: 99%